Using Infographic Through Reporting Technique to Improve Speaking Skill - Mubarok, Harir; Ramadhan, Iqbal; Anggrisia, Nur Fitria (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2022)
Nowadays, the using of learning media helps in developing learners' learning abilities. In the current digital information era, the use of digital info graphic is a learning medium to improve students' speaking skill. Info graphic is instructional learning aid that can effectively convey information quickly and easily. By combining brief information in points and graphics assist students in conveying specific topics which also develop students' speaking skill. This study used a qualitative descriptive method with case study approach. The researchers employed three instruments; observation, questionnaire, and interview. The implementation of this research involved twenty students from the English 1 subject at English Education Department UIN Maulana Malik Ibrahim Malang. The first findings revealed that the use of info graphic with reporting techniques could improve students' speaking skills, increased creativity, and ease of use for lecturer and students to transfer material. The characteristics of info graphic are comprehension, retention, and attractiveness. The second finding, students expressed a positive response of the use of info graphic aid in the online classroom. Furthermore, students are expected to apply info graphic tool to other subjects.